1991
DOI: 10.1111/j.1754-4505.1991.tb01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' willingness to provide care for patients with developmental disabilities

Abstract: This paper reports the results of a survey of School of Dental Medicine graduates at State University of New York at Stony Brook, regarding their willingness to treat patients with developmental disabilities in private practice. It also explored the influence of the DCDD program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…18,[20][21][22] Russell and Kinirons 26 surveyed community dental officers in Northern Ireland and demonstrated that, even among these dentists, lack of experience and knowledge were common reasons given by them for not offering comprehensive dental care for special needs patients including those with learning disability. A survey by Bickley 27 investigating dental hygienists' attitudes towards treating people with learning disability demonstrated that 73.5% of the respondents considered their basic training to be inadequate for such work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[20][21][22] Russell and Kinirons 26 surveyed community dental officers in Northern Ireland and demonstrated that, even among these dentists, lack of experience and knowledge were common reasons given by them for not offering comprehensive dental care for special needs patients including those with learning disability. A survey by Bickley 27 investigating dental hygienists' attitudes towards treating people with learning disability demonstrated that 73.5% of the respondents considered their basic training to be inadequate for such work.…”
Section: Discussionmentioning
confidence: 99%
“…Access to routine dental care will clearly influence the oral health of community-based patients with learning disabilities. Other barriers include some dentists' unwillingness to care for such individuals due to behavioural problems, 12,18,19 financial disincentives, 18,[20][21][22] limited physical access to dental surgeries 20,23,24 and (supposed) inadequate equipment. 12,18,21 Recently, Gordon and co-workers 25 raised the issue of the client's fear and anxiety as a major barrier for adults with learning disability receiving dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the complex needs of individuals with neurodevelopmental disability are not always being adequately met, including in routine care (Tiffreau et al, 2006) such as general healthcare and dental care (Bourke and Jago, 1983;Finger and Jedrychowski, 1989;Ferguson et al, 1991;Russell and Kinirons, 1993;Schultz et al, 2001;Waldman and Perlman, 2002;Al Agili et al, 2004) and many other areas like hospitalization (Buzio et al, 2002) and counseling for psychosocial and mental health problems (Cathels and Reddihough, 1993;Michaud et al, 2004).…”
Section: Personhood Justice Quality Of Life and Attitudes Toward Dmentioning
confidence: 99%
“…7 There have been few studies on the willingness of dental practices to provide dental care for people with handicaps. [8][9][10][11] These studies, conducted in North America, showed that approximately 20% of the dentists surveyed were willing to provide den-Willingness of dental practitioners tal care for people with handicaps.…”
Section: Introductionmentioning
confidence: 99%
“…11 These are cost, the need for special equipment, facilities, access and specialised training. However, dental care for people with handicaps is still dependent on the willingness of the dentist to treat.…”
Section: Introductionmentioning
confidence: 99%